Visual perception of noise in a simulated holographic display—A user study - Georgiou, Andreas; Kollin, Joel; Hewitt, Charlie; Chakravarthula, Praneeth; Guenter, Brian (Displays, 2022)
This work explores ways to bypass the fundamental image quality limitations of displays using Computer Generated Holograms (CGHs) and, specifically, the high-frequency noise associated with phase-only holograms. Although there is a wealth of literature on building experimental holographic systems, there are no user studies to assess the performance of a holographic system projecting a dynamic two-dimensional image. In this study, 18 participants blindly compared three groups of images displayed on a conventional monitor. The first group contained the original image, the second the simulated holographic reconstruction of the original image, and the third group had the foveated reconstruction of the original image, based on the pupil position. Holograms in the second group were computed using the Fienup algorithm and the third group using the Fienup with Perceptual Don’t Care Areas (FiPDoC) algorithm, a novel algorithm that uses eye tracking to optimize image quality in CGHs. The aim of the study was to find out if the holographic display, assuming an ideal hardware, can be as good as a conventional display and whether eye tracking can help this goal. Most participants distinguished between the original image and the un-foveated simulated reconstruction. However, the participants could not differentiate between the original image and the foveated reconstruction. Thus, foveation may be essential in designing and building the first commercial holographic displays.